Role of financial literacy in achieving financial inclusion: A review, synthesis and research agenda - Falak Khan; Muhammad Ayub Siddiqui; Salma Imtiaz (Cogent Business & Management, 2022)
Financial inclusion is an international policy agenda and can be achieved through financially literate people, who can make informed financial decisions and improve individuals' well-being. The area of Financial Literacy and Financial Inclusion is fairly highlighted in the literature; however, the collective importance of how these two areas are researched together needs scholarly attention. This paper carries out a mapping, scientometric and content analysis by compiling studies at the intersection of financial literacy and financial inclusion from a sample of 10,091 studies spread over the last 45~years and conducted on a sample of more than 850,000 individuals worldwide. We find that the number of studies increases; by fields, Finance and Economics dominate the literature; by countries, most studies come from developed countries, in particular the US; by authors, citations are skewed and by measures; studies are moving from non-functional measures to functional measures. Overall, the interest in financial literacy in bringing financial inclusion and its multifaceted role is elaborated using conceptual framework following which future research is positioned. Thus, aiding policymakers, regulators, and academicians to know the distinction of Financial literacy in Financial inclusion and to identify the potential research areas.
Keywords: 650; bibliometrics; financial inclusion; financial literacy; systematic literature review; systematic mapping study; united nations sustainable development goals (sdg); universal financial access